STRATEGI PENGELOLAAN KAMPUNG KEDUNG LUMBU SEBAGAI DAYA TARIK WISATA DI KOTA SURAKARTA - Ichwan Prastowo; Sudarmaji Sudarmaji (STABN Raden Wijaya Wonogiri, 2022)
Kedung Lumbu Village, Kliwon Market at Surakarta Municipality is in the center of the heart of the city has many historical places and buildings, all of which have the potential to be developed into an integrated tourist destination. This study aims to determine the tourism potential that exists in Kedung Lumbu village and strategies that can be used for the management of Kedung Lumbu Village sabagai tourist attractions in Surakarta City. As for this study using natiralistic qualitative methods, the data used are the result of observations, documentation, literature studies and interviews. The data used is mostly the result of interviews with informants consisting of tourism managers (Pokdarwis), local governments, tourists, and also the surrounding community. The results of some of these interviews will be analyzed by SWOT to find out the tourism potential and strategies in its management The results in this study can identify existing strengths, weaknesses, opportunities and also threats. These results can be analyzed with SWOT according to the situation and conditions in the tourist spot so that tourism potential and strategies can be obtained to take policies in the development of tourist destinations Kedung Lumbu Village, KLiwonMarket at Surakarta City. Concretely, the results of this study can be used in determining sustainable tourism, especially Kedung Lumbu Village and generally for other tourist attractions in Surakarta City.